Foreign exchange markets - Coyle, Brian (Chicago : Glenlake, New York : AMACOM, 2000)
"International trade creates a need for buying, selling or borrowing foreign currencies. This book describes the buying, selling, depositing, borrowing and lending of foreign currency. It begins by explaining how the foreign exchange markets are structured and proceeds to examine spot transactions and forward exchange contracts. Finally it explains swaps transactions and short-dated forward transaction. It is full of practical guidelines on how these transactions are made."--BOOK JACKET.
1. Introduction to the Foreign Exchange Markets -- 2. How FX Markets are Structured -- 3. Spot Transactions -- 4. Making a Spot Transaction -- 5. Practical Guidelines for Spot Transactions -- 6. Forward Exchange Contracts -- 7. Closeouts and Extensions -- 8. Swap Transactions and Short-dated Forward Transactions -- 9. Making a Forward Transaction -- 10. Practical Guidelines for Forward Transactions -- App. Currencies and their Liquidity.
Includes index.
Keywords: Foreign exchange market; International finance